The Mind's Eye 2003
DOI: 10.1016/b978-044451020-4/50013-x
|View full text |Cite
|
Sign up to set email alerts
|

On the Processing of Meaning from Parafoveal Vision During Eye Fixations in Reading

Abstract: Research dealing with parafoveal processing during eye fixations is reviewed. Four main topics are addressed: (1) parafoveal processing, (2) word skipping, (3) preview benefit effects, and (4) parafoveal-on-foveal effects. We argue that word skipping effects reflect the fact that a parafoveal word (word n+1) has been identified on the fixation on word n. We also review evidence which strongly suggests that preview benefits during reading are not due to semantic processing of a parafoveal word. Finally, we revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
126
0
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 98 publications
(138 citation statements)
references
References 67 publications
(65 reference statements)
6
126
0
4
Order By: Relevance
“…Note that the longer fixation durations in the infrequent, compared to frequent word conditions is characterised by a rightward shift in the distribution, consistent with previous studies (Rayner, 1995;Rayner, Liversedge et al, 2003). Numerical differences in the distributions between the frequent and infrequent orthographically familiar conditions occur no earlier than differences in the distributions between the orthographically familiar and unfamiliar infrequent word conditions.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…Note that the longer fixation durations in the infrequent, compared to frequent word conditions is characterised by a rightward shift in the distribution, consistent with previous studies (Rayner, 1995;Rayner, Liversedge et al, 2003). Numerical differences in the distributions between the frequent and infrequent orthographically familiar conditions occur no earlier than differences in the distributions between the orthographically familiar and unfamiliar infrequent word conditions.…”
Section: Resultssupporting
confidence: 90%
“…In contrast, for both sets of analyses for orthographically familiar words there was no difference in prior fixation duration between the frequent and infrequent conditions (ts < 1). 6 It has been suggested that parafoveal-on-foveal effects can sometimes occur as a result of inaccurate saccade targeting (Drieghe et al, 2007;Rayner, Warren et al, 2004;Rayner, White et al, 2003). However, if the parafoveal-on-foveal effects reported above had arisen due to mistargeting of saccades, then there perhaps also should have been a parafoveal-on-foveal effect of word frequency.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations